Tractor service providers in Myanmar: Early insights from the 2025 monsoon season - Masias, Ian; Htar, May Thet; Oo, Theingi (International Food Policy Research Institute, 2025)
This note presents results from a July–August 2025 phone survey of 401 tractor service providers (TSPs)—who play a vital role in enabling timely land preparation and planting— offering early insights into the 2025 monsoon season.